Analytical method of sizing photovoltaic water pumping system - FIFATIN, François-Xavier; ACAKPOVI, Amevi; AWUAH-BAFFOUR, Robert (My University, 2012)
Photovoltaic Water Pumping System (PWPS) is a well known technology deployed in remote areas for the provision of drinking water and also for irrigation. Due to the high cost of solar energy implementation, the system becomes very costly. Unfortunately, innaccuracies in the system sizing mostly lead to oversizing, resulting in huge waste of money. This paper presents a mathematical method of sizing photovoltaic water pumping systems with more accuracy. The method starts with the assessment of losses through pipes and other accessories by using Poiseuil, Blasius and Blench laws. It also considers data on solar irradiation, average temperature as well as necessary parameters on the solar panel itself. It helps to calculate accurately the peak power that must be generated according to a demand. Moreover, simulations have been done in MATLAB to emphasize the effect of neglecting the temperature, the solar irradiation and the pipeline losses on the sizing method. Results show that big variations of temperature inﬂuence the sizing negatively, requiring more power than necessary; Bigger Solar irradiation requires fewer peak power. Again, hydraulic losses could add up to 10% of the necessary peak power.
Keywords: Solar Irradiation; Temperature; Pumping system; Peak Power; Hydraulic losses; Simulation.